IMPLEMENTATION OF THE REGION DEVELOPMENT STRATEGY: PROGRAM-TARGETING APPROACH AND INNOVATION ASPECT - І.М. Літвінова; Н.О. Держак; Д.В. Заблодська (Економіка та право)
The article describes the vision of development strategy implementation of region with the help of program-target approach and taking into account the innovative aspect. It is established that the strategic goals, defined in the Development Strategy of any region, should be realized through a system of operational goals, which are aimed at solving the problems both for the region as a whole and for the individual territories – districts, territorial communities, cities, towns, villages. To achieve the strategic goals, the Action Plan is loosened, the formation of which uses technical projects that are important for the development of region, are in line with the strategy and must be implemented based on the powers of the regional executive bodies, local governments and the resources that may be involved. It is established that for implementation of Development Strategy of Luhansk region until 2027, four programs have been developed, within which projects of regional development are implemented. Plan for the implementation of the Luhansk Regional Development Strategy and the Luhansk Regional Development Strategy itself contain innovative elements: operational goals, objectives, indicators, technical projects, technologies, etc. The article provides a visualization of the implementation of program-based approach and innovative aspect in the implementation of the regional development strategy.